2012
DOI: 10.1016/j.physbeh.2011.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation in adolescence alters behaviors in the forced swim and sucrose preference tests in female but not in male rats

Abstract: Social interactions in rodents are rewarding and motivating and social isolation is aversive. Accumulating evidence suggests that disruption of the social environment in adolescence has long-term effects on social interactions, on anxiety-like behavior and on stress reactivity. In previous work we showed that adolescent isolation produced increased reactivity to acute and to repeated stress in female rats, whereas lower corticosterone responses to acute stress and decreased anxiety-related behavior were noted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(50 citation statements)
references
References 39 publications
10
40
0
Order By: Relevance
“…Isolation rearing for longer periods (weaning to late adolescence) in rats increased immobility in the FST, although these subjects also received saline injections during preweanling stages (Kuramochi & Nakamura, 2009). The same results were observed in noninjected social isolates (Brenes, Padilla, & Fornaguera, 2009), although no enduring effect on immobility has been reported (Hong et al, 2012). These effects were lower in animals raised in an enriched environment.…”
Section: Clinical and Clinically Relevant Findingssupporting
confidence: 76%
See 1 more Smart Citation
“…Isolation rearing for longer periods (weaning to late adolescence) in rats increased immobility in the FST, although these subjects also received saline injections during preweanling stages (Kuramochi & Nakamura, 2009). The same results were observed in noninjected social isolates (Brenes, Padilla, & Fornaguera, 2009), although no enduring effect on immobility has been reported (Hong et al, 2012). These effects were lower in animals raised in an enriched environment.…”
Section: Clinical and Clinically Relevant Findingssupporting
confidence: 76%
“…In a separate study, these effects were not observed in males, but in female adult rats that were isolated (Hong et al, 2012). These effects may also depend on the strain of rat used.…”
Section: Clinical and Clinically Relevant Findingsmentioning
confidence: 81%
“…Following habituation, rats were given one bottle with 1% sucrose (Sigma Aldrich) solution and the second bottle with tap water. The position of the sucrose bottle was alternated to avoid side preferences (Hong et al 2012). Bottles were weighed within 1 h after lights on and again within 1 h before lights off.…”
Section: Methodsmentioning
confidence: 99%
“…Sucrose is highly preferable to rats; hence, decreases in consumption of sucrose reflect a decreased sensitivity to normally rewarding stimuli, anhedonia, a major symptom of depression. 32 …”
Section: Sucrose Preference Testmentioning
confidence: 99%